Olfactory Dysfunction and Its Association With Neuropathologic Proteins in Cerebrospinal Fluid From Patients With Parkinson Disease - Guo, Peng; Wang, Rui-dan; Lian, Teng-hong; Ding, Du-yu; Zhang, Ya-nan; Zhang, Wei-Jiao; Li, Dan-ning; Li, Li-xia; Li, Jing-hui; Guan, Hui-ying; Yu, Shu-yang; Liu, Li; et al. (Frontiers in Aging Neuroscience, 2020)
Background and Purpose: Olfactory dysfunction (OD) is a common non-motor symptom of Parkinson disease (PD). However, the relationship between OD and neuropathologic proteins in cerebrospinal fluid (CSF) from PD patients remains unclear. Methods: 166 PD patients were included in the study. Overall olfactory function was assessed by summing up the scores of olfactory threshold, discrimination, and identification by a Sniffin' Sticks test, based on which, patients were divided into PD with OD (PD-OD) and PD with no OD (PD-NOD) groups. CSF samples were obtained from 76 PD patients. The levels of neuropathologic proteins, including α-Synuclein, Aβ1-42, total tau (T-tau), and multiple forms of phosphorylated tau (P-tau) in CSF were measured by an enzyme-linked immunosorbent assay. Results: out of the 166 PD patients, 103 cases (62.0%) had OD. The scores of overall olfactory functions, and olfactory threshold, discrimination, and identification in the PD-OD group were all significantly lower than that in the PD-NOD group (P < 0.001). α-Synuclein level in CSF was significantly higher in the PD-OD group than the PD-NOD group (P < 0.05), and was significantly and negatively correlated with the scores of overall olfactory function, and olfactory discrimination and identification (P < 0.05). Aβ1-42 level in CSF was higher in the PD-OD group than the PD-NOD group, and was significantly and negatively correlated with the olfactory identification score (P < 0.05). T-tau level in CSF was significantly lower in the PD-OD group than the PD-NOD group (P < 0.05), and was significantly and positively correlated with the olfactory discrimination score (P < 0.05). There was no significant difference in P-tau level in CSF between the PD-OD and PD-NOD groups and no correlation between OD score and P-tau level in CSF. Conclusions: PD-OD includes the impairments of olfactory threshold, discrimination, and identification, and is associated with the significant elevation of α-Synuclein and the decrease of the T-tau level in CSF.